Utilizing Mixed Research Methods to Develop a Quantitative Assessment Tool: An Example From Explosive Remnants of a War Clearance Program - Durham, J.; Tan, Boon; White, R. (Sage Publishing, 2011)
This article outlines the process of developing a quantitative instrument and livelihood assetindex. The intent of the index was to assess household perspectives of the impact of the removalof explosive remnants of war on livelihoods. Conducted in the Lao People's Democratic Republic,the study used a sequential mixed methods design. It began with a qualitative component, whichinformed instrument development. The article discusses the instrument development processand some of the challenges faced. These included developing a reliable livelihood asset index andfinding the limitations of quantitative indexes in this setting. Another challenge was reconcilingtensions in mixing methods informed by different worldviews.